GREEN SYNTHESIS OF SILVER NANOPARTICLES USING MANGROVE FRUIT POLYSACCHARIDE FOR BACTERIAL GROWTH INHIBITION: GREEN SYNTHESIS OF SILVER NANOPARTICLES - GAJENDRA NATH MAITY,; JOY SARKAR,; SOMANJANA KHATUA,; SOUMITRA MONDAL,; KRISHNENDU ACHARYA, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to find out the antibacterial activity of the silver nanoparticles (Ag-NPs) using a low-cost green synthesis approach for the formulation of Ag-NPs applying polysaccharide extracted from the fruits of a mangrove plant of Sundarban. Methods: Fresh and healthy fruits were collected from Ceriops decandra plant. Sufficient amount of carbohydrates was extracted from those fruits and the physicochemical characterization of the polysaccharide was analyzed by gas chromatography–mass spectrometry and Fourier-transform infrared spectrophotometry. The respective polysaccharide was further applied to generate the Ag-NPs which were characterized by UV visible, dynamic light scattering, transmission electron microscopy, EDAX, and X-ray diffraction. The antibacterial efficacy of the Ag-NPs was also determined against some pathogenic Gram-negative and Gram-positive bacteria using the microdilution method. Results: Glucose and galactose are the major monomers among the extracted carbohydrates. Various types of spectral analysis confirmed the formation of Ag-NPs. The green synthesized Ag-NPs have the average diameter of about 28 nm. Furthermore, the green synthesized Ag-NPs exhibited strong antibacterial activity against some pathogenic Gram-positive (L. cytomonogenes, Bacillus Subtilis, and Staphylococcus aureus) and Gram-negative (Salmonella typhimurium and Escherichia coli) bacteria. Conclusion: The green synthesis of Ag-NPs using plant polysaccharide was an environment-friendly and cost-effective method as compared to the conventional physical and chemical synthesis techniques.